1971
DOI: 10.1063/1.1659782
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Recrystallization in Thick Bias-Sputtered Copper Deposits

Abstract: Deposits of copper up to 1 mm thick were formed at room temperature in a triode sputtering apparatus using a krypton discharge under various conditions of sputtering rate, gas purity, and substrate bias. Room-temperature recrystallization and grain growth displaying no twins were observed within 9 h after removal from the sputtering apparatus. This resulted in a dominant orientation of {100} planes parallel to the substrate-deposit interface. Recrystallization rate increased as a function of increasing deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(42 citation statements)
references
References 6 publications
4
38
0
Order By: Relevance
“…Contrary to popular belief, the self-annealing phenomenon for Cu is not a unique consequence of the electroplating process. Although there is early work by Patten et al [101] describing microstructural evolution during the storage of sputtered deposited Cu films, room-temperature, self-annealing has not been widely observed in physical vapour deposited copper [102]. Recently, Rossnagel et al [103] and Bernat et al [104] showed that the resistivity in sputtered deposited copper films (with thickness below 100nm) descreases during storage after deposition.…”
Section: Self-annealing In Electroplated and Sputtered Copper Filmsmentioning
confidence: 99%
“…Contrary to popular belief, the self-annealing phenomenon for Cu is not a unique consequence of the electroplating process. Although there is early work by Patten et al [101] describing microstructural evolution during the storage of sputtered deposited Cu films, room-temperature, self-annealing has not been widely observed in physical vapour deposited copper [102]. Recently, Rossnagel et al [103] and Bernat et al [104] showed that the resistivity in sputtered deposited copper films (with thickness below 100nm) descreases during storage after deposition.…”
Section: Self-annealing In Electroplated and Sputtered Copper Filmsmentioning
confidence: 99%
“…Patten et al [24] formed deposits of Cu up to 1mm in thickness at room temperature in a triode sputtering apparatus using a krypton discharge under various conditions of sputtering rate, gas purity, and substrate bias. The 3.81 cm diameter target was made from commercial grade OFHC forged Cu-bar stock containing approximately 100 ppm oxygen by weight with only traces of other elements.…”
Section: Copper and Silver Vapor-depositsmentioning
confidence: 99%
“…Current research on sputtered films deposited with a bias voltage is based mostly on thin films (<300 nm) with FCC and BCC structures. Patten et al study the effects of a small substrate bias (À70 V) on the microstructure of thick Cu and Cr films (up to 1.0 mm) [19,20], however there is no measure of residual stresses. For thin films, there are a few samples of the effects of bias on the residual stresses.…”
Section: Residual Stress Resultsmentioning
confidence: 99%
“…Literature on thick films (25 lm) is very sparse with few exceptions [8,19]. Current research on sputtered films deposited with a bias voltage is based mostly on thin films (<300 nm) with FCC and BCC structures.…”
Section: Residual Stress Resultsmentioning
confidence: 99%